Generating evidence for diagnosis and therapy of RarE LIVEr disease: the RELIVE Initiative for systematic reviews and meta-analyses - Fuchs, Juri; Murtha-Lemekhova, Anastasia; Pfeiffenberger, Jan; Fichtner, Alexander; Günther, Patrick; Halama, Niels; Mayer, Philipp; Hornuß, Daniel; Klotz, Rosa; Probst, Pascal; Hoffmann, Katrin (Systematic Reviews, 2022)
Rare liver lesions and diseases have seldomly aroused major interest of researchers. For most guidelines, presumably similar clinical conditions are pooled without detailed investigations of singularities that they present.